Determination of Causative Human Papillomavirus Type in Tissue Specimens of Common Warts Based on Estimated Viral Loads - Breznik, Vesna; Fujs Komloš, Kristina; Hošnjak, Lea; Luzar, Boštjan; Kavalar, Rajko; Miljković, Jovan; Poljak, Mario (Frontiers in Cellular and Infection Microbiology, 2020)
Background. Assessment of human papillomavirus (HPV) type-specific viral load (VL) is a valid tool for determining the etiology of HPV-related skin tumors, especially when more than one HPV type is detected within one lesion. Methods. The causative HPV type was determined in 185 fresh-frozen tissue specimens of histologically confirmed common warts (CWs) collected from 121 immunocompetent patients. All tissues were tested using the type-specific quantitative real-time polymerase chain reactions (PCR) for the most common wart-associated Alpha-PV (HPV2/27/57) and Mu-PV types (HPV1/63/204). The presence of 23 additional low-risk HPVs was evaluated using a conventional wide-spectrum PCR. Results. HPV DNA was detected in 176/185 (95.1%) CWs and multiple HPV types in 71/185 (38.4%) lesions. Using the VL approach and a robust cutoff of one viral copy/cell established in this study, HPV2/27/57 were determined as causative agents in 41/53 (77.3%) and 53/71 (74.7%) CWs with single and multiple HPVs, respectively. Conclusions. CWs are mostly etiologically associated with HPV2/27/57 and only rarely with HPV1. In the majority of CWs containing multiple HPVs, a single HPV type was present in high concentration, indicating etiological association. No significant differences in VLs of lesion-causing HPV types in CWs containing single or multiple HPVs were found.